KEANEKARAGAMAN IKAN BADA (Pisces: Rasbora) DI SUNGAI KUMU PASIR PENGARAIAN ROKAN HULU RIAU - Roza, Elmi; Purnama, Arief Anthonius; Ade, Filza Yulina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study on diversity of bada fish (Pisces: Rasbora) in Kumu River Pasir Pengaraian Rokan Hulu, Riau has been conducted from July to September 2014 by using the survey method. Samples were collected with gill nets, acting nets, hooks and trap by stratified sampling method with three repetitions in upperstream, middlestream, and downstream. Result showed, five species were found as Rasbora caudimaculata, R. argyrotaenia, R. trilineata, R. elegans, and R. rutteni. The environmental factors that affect diversity of the fish were temperature, pH, depth, current speed, DO, BOD5, and CO2, while the TSS was not affect.